Ferroptosis: A New Strategy for Cancer Therapy - Chen, Yu; Fan, Zhihua; Hu, Shen; Lu, Chengchao; Xiang, Yi; Liao, Shuzhi (Frontiers in Oncology, 2022)
Ferroptosis is a newly discovered form of iron-dependent cell death，which is different from other death forms. The main characteristics of ferroptosis are: (1) Amino acid metabolism. (2) Iron metabolism; (3) Lipid metabolism and Reactive oxygen species（ROS）. Ferroptosis is related to the occurrence and development of a variety of cancers, especially in the drug resistance. This article reviews the research progress of iron death in tumors, and provides a theoretical reference for its further research and clinical application.